2017
DOI: 10.21037/tgh.2017.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative staging of nodal status in gastric cancer

Abstract: An accurate preoperative staging of nodal status is crucial in gastric cancer, because it has a great impact on prognosis and therapeutic decision-making. Different staging methods have been evaluated for gastric cancer in order to predict nodal involvement. So far, no technique could meet the necessary requirements, which include a high detection rate of infiltrated lymph nodes and a low frequency of falsepositive results. This article summarizes different staging methods used to assess lymph node status in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(33 reference statements)
0
10
0
2
Order By: Relevance
“…The cT and cN status was defined by clinical assessment with computerized tomography by an experienced radiologist. Lymph nodes more than 10 mm in the smallest axis were considered metastatic 15,16 . The T assessment was defined in accordance with the 8th edition of the UICC Staging System 17,18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cT and cN status was defined by clinical assessment with computerized tomography by an experienced radiologist. Lymph nodes more than 10 mm in the smallest axis were considered metastatic 15,16 . The T assessment was defined in accordance with the 8th edition of the UICC Staging System 17,18…”
Section: Methodsmentioning
confidence: 99%
“…Lymph nodes more than 10 mm in the smallest axis were considered metastatic. 15,16 The T assessment was defined in accordance with the 8th edition of the UICC Staging System. 17,18 The type of gastrectomy and lymphadenectomy were defined based on the Japanese Gastric Cancer Association criteria, 19 Complications were categorized based on the Clavien-Dindo classification system and major complications were defined as Clavien >II.…”
Section: Methodsmentioning
confidence: 99%
“…Computed tomography (CT) is widely recognized as the primary method for staging and detecting distant metastases, determining surgical treatment [21]. Accuracy of preoperative cN staging is strongly dependent on cT stage and histological type of GC [22].…”
Section: Computed Tomographymentioning
confidence: 99%
“…A German study showed that even 55% of cancerous-infiltrated LN remain smaller than 5 mm [26], which implies high possibility of false-negative and false-positive results. Limitations are related to poor visualisation of nodal engagement [21,27], nodal location dependency and sensitivity rate of 44.4% [22]. Moreover, in up to 30% of negative CT scans, endoscopic ultrasound (EUS) reveals nodal involvement [27,28].…”
Section: Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation